KEWENANGAN SATUAN POLISI PAMONG PRAJA (SATPOL PP) DALAM PENANGANAN WARGA PENDATANG DI KABUPATEN BADUNG - Michael Calvirad Meo Ghari (Yayasan Nusantara Hasana Berdikari, 2023)
Public order and public peace are basic needs that people always expect in carrying out their daily activities. Therefore, people really yearn for the belief that they will be safe from all forms of actions, actions and intimidation that lead to and cause things that will destroy the order of social life, which are carried out by individuals and / or certain other parties. Based on the background of the problem, the formulation of the problem is as follows: What is the Authority of the Civil Service Police Unit in Handling Migrants in Badung Regency? What factors are the obstacles for the Civil Service Police Unit to curb and deal with migrants in Badung Regency. The objectives of this study are as follows: To determine the authority of the Civil Service Police Unit in Handling Newcomers and To find out what obstacles the Civil Service Police Unit faces in dealing with immigrants. The research method is field research, the research specification used in this research is descriptive. research that collects data is carried out in the field, such as in the community, civil society organizations and organizations and government agencies. The results of this study can be seen that the authority of the Civil Service Police Unit of Badung Regency as a regional apparatus has played a very strategic role in strengthening regional autonomy and public services to realize security, comfort, peace, and order has been going well. To ensure the implementation of the duties of the Civil Service Police Unit in enforcing regional regulations and regional head regulations, the administration of public order and peace and protection of the community continues to improve, both in terms of institutions and human resources. Obstacles The civil service police unit is also known that Violations of Regional Regulations in Badung Regency are indeed difficult to overcome, mostly in the socio-cultural field, such as residents who have registered and illegal citizens without an identity if they have been arrested for a few days there will definitely be more newcomers, maybe this is due to legal sanctions very light offense.